2016
DOI: 10.1002/2016tc004230
|View full text |Cite
|
Sign up to set email alerts
|

The tectonics of the western Ordos Plateau, Ningxia, China: Slip rates on the Luoshan and East Helanshan Faults

Abstract: Analysis of the locus, style, and rate of faulting is fundamental to understanding the kinematics of continental deformation. The Ordos Plateau lies to the northeast of Tibet, within the India‐Eurasia collision zone. Previous studies have suggested that it behaves rigidly and rotates anticlockwise within a large‐scale zone of ENE‐WSW left‐lateral shearing. For this rotation to be accommodated, the eastern and western margins of the Ordos Plateau should be undergoing right‐lateral shearing and yet the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 89 publications
3
29
0
Order By: Relevance
“…(2018), where most of the left‐lateral slip of the Haiyuan fault is accommodated by contraction across the Liupanshan Mountains, and the remaining part is transferred through the South Liupanshan fault to the subparallel Qishan‐Mazhao fault. In sum, we speculate that the observed kinematic deformation pattern around the Ordos block is a result of a combination of the sinistral shear to the south and north of the Ordos block and the push on its southwest margin from the Tibetan Plateau (Middleton et al., 2016; Xu & Ma, 1992; Zhang et al., 1998).…”
Section: Discussionmentioning
confidence: 86%
“…(2018), where most of the left‐lateral slip of the Haiyuan fault is accommodated by contraction across the Liupanshan Mountains, and the remaining part is transferred through the South Liupanshan fault to the subparallel Qishan‐Mazhao fault. In sum, we speculate that the observed kinematic deformation pattern around the Ordos block is a result of a combination of the sinistral shear to the south and north of the Ordos block and the push on its southwest margin from the Tibetan Plateau (Middleton et al., 2016; Xu & Ma, 1992; Zhang et al., 1998).…”
Section: Discussionmentioning
confidence: 86%
“…However, the timing of thrust initiation and onset of the strike‐slip of the Tianjingshan Fault are still unclear. The Niushoushan–Luoshan Fault, which lies to the east of the Yantongshan–Yaoshan Fault—the foremost boundary of the north‐eastern Tibetan Plateau—is a dextral strike‐slip that consists of numerous secondary faults (Lei et al, 2016; Middleton et al, 2016; Shi et al, 2015). Recent studies showed a Late Quaternary right‐lateral slip rate of 0.4 mm/a (Lei et al, 2016), and an average right‐lateral slip rate of 4.3 ± 0.4 mm/a on the Luoshan Fault (Middleton et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…In this model, the Ordos block does not undergo anticlockwise rotation. Geological investigations have indicated the presence of dextral shear along the Yinchuan and Shanxi grabens on the western and eastern margins of the block (Middleton et al., 2016; Xu et al., 1994; B. Zhang et al., 1986), while the Weihe and Hetao grabens show no evidence of lateral motion of any kind (Lin et al., 2015; Ran et al., 2003).…”
Section: Introductionmentioning
confidence: 99%